The effect of child care on family structure: Theory and evidence - Stefan Bauernschuster; Rainald Borck (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper studies the effect of child care provision on family structure. We present a model of a marriage market with positive assortative matching, where in equilibrium the poorest women stay single. Couples have to decide on the number of children and spousal specialization in home production of public goods and child care. We then study how child care provision affects the equilibrium. Due to specialization in home production, the incentive to use child care is smaller for married mothers than for single mothers. We show that this increases the number of single mothers and the divorce rate. Using survey data from Germany, we also present empirical evidence which is consistent with this finding.
Keywords: J12; J13; 330; marriage; divorce; single parenthood; child care; Kinderbetreuung; Familienökonomik; Haushaltsproduktion; Scheidung; Ehe; Alleinerziehende; Theorie; Deutschland